A new tritiated water measurement method with plastic scintillator pellets†. Issue 4 (3rd July 2016) - Furuta, Etsuko; Iwasaki, Noriko; Kato, Yuka; Tomozoe, Yusuke
ABSTRACT: A new tritiated water measurement method with plastic scintillator pellets (PS-pellets) by using a conventional liquid scintillation counter was developed. The PS-pellets used were 3 mm in both diameter and length. A low potassium glass vial was filled full with the pellets, and tritiated water was applied to the vial from 5 to 100 μl. Then, the sample solution was scattered in the interstices of the pellets in a vial. This method needs no liquid scintillator, so no liquid organic waste fluid is generated. The counting efficiency with the pellets was approximately 48 % when a 5 μl solution was used, which was higher than that of conventional measurement using liquid scintillator. The relationship between count rate and activity showed good linearity. The pellets were able to be used repeatedly, so few solid wastes are generated with this method. The PS-pellets are useful for tritiated water measurement; however, it is necessary to develop a new device which can be applied to a larger volume and measure low level concentration like an environmental application.